Effect of Adding Different Levels of Flaxseed Oil to Diets on The Rate of Mass and Individual Motility of Spermatozoa in Ostrich Semen - Ali, Nashwan Majeed (American Journal of Botany and Bioengineering, 2025)
This study was conducted at the Babylon Reserve for Ostrich, Falcon, and Deer Breeding, located in Al-Musayyab District, Al-Hindiya Subdistrict, Babylon Province, to investigate the effect of adding flaxseed oil to ostrich diets at inclusion levels of 1% and 2% on the mass and individual sperm motility in ostrich semen. A total of 27 sexually mature ostriches were used in the study and were randomly allocated into three treatment groups, each with three replicates. A standardized diet was provided to both males and females, containing 17.34% crude protein and an energy level of 2740.56 kcal of metabolizable energy per kg of feed, offered twice daily (morning and evening). The study involved an evaluation of semen characteristics, specifically focusing on mass and individual sperm motility. The results indicated significant to highly significant improvements in most evaluated parameters across the treatment periods. These findings suggest that flaxseed oil, as a rich source of omega-3 fatty acids, can effectively enhance reproductive performance in ostriches.